Dancing home - Collis, Paul (University of Queensland Press, 2017)
"When he was in gaol, he'd begun to prepare himself for the fight of his life, a showdown with the policeman, McWilliams ⁵ he'd face life with death, and see who blinked first." Blackie and Rips are fresh out of prison when they set off on a road trip back to Wiradjuri country with their mate Carlos. Blackie is out for revenge against the cop who put him in prison on false grounds. He is also craving to reconnect with his grandmother's country. Driven by his hunger for drugs and payback, Blackie reaches dark places of both mystery and beauty as he searches for peace. He is willing to pay for that peace with his own life. Part road-movie, part 'Koori-noir', Dancing Home announces an original and darkly funny new voice